Clinicopathological features and survival for gallbladder NEN: a population-based study. Issue 9 (September 2019) - Cen, Dong; Liu, Hui; Wan, Zhe; Lin, Zhongjie; Wang, Yanting; Xu, Junjie; Liang, Yuelong
Abstract : Purpose: Gallbladder neuroendocrine neoplasm (GB-NEN) is a relatively rare neoplasm, accounting for 0.5% of all neuroendocrine neoplasm cases and 2.1% of gallbladder cancers. Because of the limited understanding of GB-NEN, the aim of this study was to explore the clinicopathology and survival of GB-NEN patients selected from the Surveillance, Epidemiology, and End Results (SEER) database. Methods: A total of 248 GB-NEN patients from the SEER database diagnosed between 2004 and 2015 were included. Kaplan–Meier curves were used to examine the survival time. Multivariate Cox proportional hazard models were used to estimate hazard ratios with 95% confidence intervals to analyze the impact of factors on overall survival and cancer-specific survival. Results: The majority of the GB-NEN patients were women (67.3%), white (77%), and married (61.7%). Most tumors were <2 cm in size (31.0%), G3 stage (25.8%), and distant SEER stage (41.1%). 62.9% and 64.5% of cases showed an absence of lymph node metastasis and tumor metastasis, respectively. Patients who received gallbladder surgery had significantly better survival outcomes ( P < 0.001). However, patients who received both gallbladder surgery and lymph node resection did not have better survival outcome compared with patients who received only gallbladder surgery. Multivariate Cox proportional hazard models indicated that older age, unmarried status, large tumor size (>5 cm), and distant SEER stage were significant independent predictors for decreased overall survival time and cancer-specific survival time ( P < 0.05). Conclusion: Age, marital status, tumor size, and SEER stage were predictors for the survival of GB-NEN patients. Gallbladder surgery was associated with better survival, but the combination of gallbladder surgery and lymphadenectomy had no effect on survival outcomes.